How to Be a Super Model: Using Role Modeling to Become an Exemplary Educator - Priti Bhansali; Geeta Singhal; Melissa Held; Helen Fromme (Association of American Medical Colleges, 2014)
Abstract Over the past several years, published studies have described the qualities and skills of exemplary medical educators. Despite its inclusion in these lists, role-modeling is a skill that is not often developed for use as an educational method. The purpose of this workshop is to assist participants in better understanding the characteristics of effective role-modeling and create a paradigm for how to consciously incorporate it into the daily education of students, residents, and colleagues in varied domains, including teaching, professionalism, communication, and patient care. In this workshop, participants are introduced to the concept of role-modeling as a metacognitive process where successful educators make their thought processes and reasons for behaviors accessible to learners. Through an interactive icebreaker, participants discuss role-modeling behaviors that they have encountered, and reflect on their own professional development, describing the impact of positive and negative role-modeled behaviors observed through their training. Participants are then provided a succinct review of the literature on role-modeling as an educational method in order to provide a framework for participants' active experimentation in breakout sessions. During these small-group sessions, participants explore the different contexts in which they currently may role model teaching, professionalism, communication, and clinical behaviors. Finally, participants collaborate to develop practical strategies for utilizing role modeling in the daily practice of education using the framework provided, and then share their strategies with the larger group. This workshop has been selected for presentation to national audiences at the Pediatric Academic Society (PAS) Meeting in 2013, The Committee on Medical Student Education in Pediatrics (COMSEP) Meeting in 2012, and the American Academy of Pediatrics Pediatric Hospital Medicine Conference (PHM) in both 2012 and 2013. In addition, this workshop has been adapted by the authors for presentation at their local institutions for Grand Rounds, a faculty development retreat, a workshop for faculty and senior medical student preceptors of a Principles of Clinical Medicine course for first and second year medical students, and for pediatric residents learning leadership and teaching skills during a Global Child Health elective. We have also adapted the small group exercise to discuss other topics, such as professionalism, breaking bad news, and working with the angry/upset family.